CEO Characteristics: Navigating Accounting Conservatism Via Technology And Information Investment - Sari Lestari; Mutmainah, Siti; Raharja, Surya (Jurnal Akuntansi, 2024)
The study examined the influence of CEO characteristics, including educational background and gender, on accounting conservatism. The study used a quantitative approach. The population was in the banking sector from 2020 to 2022. The study selected 40 companies through purposive sampling, resulting in 120 observations data. The research collected data from audited financial and annual reports, available on www.idx.co.id. The data were analysed using path analysis facilitated by Smart PLS. The findings indicate that the CEO's educational background and gender do not influence accounting conservatism. CEOs with educational backgrounds in accounting and related fields negatively influence technology and information investment, as do female CEOs. Technology and information investment influence accounting conservatism. Interestingly, technology and information investment mediate between female CEOs and accounting conservatism, while educational background does not. Decision-makers in the banking sector can leverage these findings to design strategic decisions.